1996
DOI: 10.4315/0362-028x-59.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Shiga-Like Toxin-Producing Escherichia coli in Ground Beef and Milk by Commercial Enzyme Immunoassay

Abstract: Shiga-like toxin (SLT)-producing Escherichia coli (SLTEC) is the leading cause of acute renal failure among children. SLTEC are most commonly ingested from contaminated food, and because cattle are a major reservoir, ground beef and milk have been a significant source of contamination associated with multiperson outbreaks. While serotype O157:H7 has been principally identified in the United States there are many other SLTEC serotypes associated with human disease. We have therefore examined the utility of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…These results imply that EHEC is one of the major sources of beef contamination, unlike the other pathogenic E. coli. National surveys have also observed STEC in raw or ground beef at rates ranging from 15% to 25% (Acheson et al, 1996;Samadpour et al, 2002;Adwan and Adwan, 2004). In contrast, the prevalence rates in ground beef from other previous studies showed lower values than the range observed in our study.…”
Section: Microbiological Analysis and Prevalence Of Ehec In Frozen Mecontrasting
confidence: 85%
“…These results imply that EHEC is one of the major sources of beef contamination, unlike the other pathogenic E. coli. National surveys have also observed STEC in raw or ground beef at rates ranging from 15% to 25% (Acheson et al, 1996;Samadpour et al, 2002;Adwan and Adwan, 2004). In contrast, the prevalence rates in ground beef from other previous studies showed lower values than the range observed in our study.…”
Section: Microbiological Analysis and Prevalence Of Ehec In Frozen Mecontrasting
confidence: 85%
“…In this regard, it is noteworthy that, in several studies that attempted to address the pathogenicity of non-O157:H7 STEC, control subjects without diarrhea had the same frequency of fecal excretion of non-O157:H7 STEC as did patients with diarrhea [51][52][53][54][55]. Non-O157:H7 STEC are quite common in food [56,57], in contrast to the comparative rarity of O157:H7 STEC [58]. Thus, human contact with non-O157:H7 STEC is probably frequent, and it is possible that, in some patients, the recovery of non-O157:H7 STEC in the stool reflects innocuous gastrointestinal pass-though and not infection.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid methods able to identify E. coli O157:H7 in foods or faecal specimens are directed towards immunological or genetic targets. Although immunoassays are more rapid and less labour intensive than cultural techniques (Acheson et al 1996), they are inadequate as independent procedures. Furthermore, false positives are not uncommon when interpreting immunoassay test results, and further confirmation is required.…”
Section: Introductionmentioning
confidence: 99%